Implementing Multimodal Paralanguage by the ELT Students in Presentational Activity - Rezza Fatwassani; Januarius Mujiyanto; Rudi Hartono; Puji Astuti (Universitas Negeri Semarang, 2022)
Abstrak. Multimodal paralanguage is related to multi resources of nonphonemic properties in communication activities. As part of the non-verbal aspect, paralanguage is considered a crucial technique for the success of the presentational activity. In this case, a group of ELT students at a certain university had concerns about transferring information that caused their presentation performance. Therefore, this study aims to reveal the implementation of paralanguage components by entailing multimodal features in conveying effective meaning. The subject of this study is a representative group of ELT students at a certain university. Qualitative research is used with observation and recording as the data collection method. The steps in analyzing the data are adopted from Miles, Huberman, and Saldana (2014), including data collection, data reduction, data display, and conclusion (drawing or verifying). The findings revealed distinctive components of paralanguage used by the students during the presentation. The implemented components include voice qualities, vocal characteristics, and vocal segregation. Multimodal features are implemented as a strategy for improvisation in communication. Furthermore, this study can be advantageous as a reference for each person who will act as a presenter or speaker to enhance their presentational skill.